A scoping review of interventions using occupation to improve mental health or mental wellbeing in adolescent populations. (March 2023) - Parsonage-Harrison, Jackie; Birken, Mary; Harley, David; Dawes, Helen; Eklund, Mona
Introduction: Occupation-based interventions could help to address a growing mental health crisis among young people and adolescents. To develop new interventions and avoid research waste, a review of the academic literature is needed that systematically identifies and describes interventions designed to improve the mental health and wellbeing of 11–25 year-olds. Aim: The scoping review aims to systematically review the academic, literature to identify and describe key characteristics of intervention studies using occupation to improve adolescents' and young people's mental health and wellbeing, exploring the range of interventions, reviewing reporting quality and illuminating gaps for further research. Method: An iteratively developed scoping review protocol informs a systematic database search and review of the literature. Core characteristics are extracted and described, using the TIDIER guidelines and the CASP assessment tool. Results: Five occupational therapy-based interventions, and 69 other occupation-based studies representing a wide breadth of approaches, outcomes and settings were identified. Conclusions: Robust development, testing and reporting of occupation-based and occupation-focused intervention studies to promote and support mental health and wellbeing in adolescents and young people are needed. Interventions should be co-designed, developmentally appropriate and scaffold development. However, better agreement is needed about core outcomes measurement in this area.